Vasicinone, a pyrroloquinazoline alkaloid from Adhatoda vasica Nees enhances memory and cognition by inhibiting cholinesterases in Alzheimer's disease - Kancharla Bhanukiran; Ravi Singh; Gajendra T A; Kakarla Ramakrishna; Sushil Kumar Singh; Sairam Krishnamurthy; Ashok Kumar; Siva Hemalatha (Elsevier, 2023)
Background: Alzheimer's disease (AD) is a neurodegenerative disease with cognitive and memory decline. Due to the lack of effective treatment for AD, there is an interest in finding novel compounds to treat AD. The leaves of Adhatoda vasica Nees (AV) exhibited anti-AD effects and known to be rich in pyrroloquinazoline alkaloids. However, the role of pyrroloquinazoline alkaloids as an anti-AD was not explored. Therefore, the present study aimed to isolate active pyrroloquinazoline alkaloids through bioactivity guided fractionation from AV to explore their anti-AD effect. Method: Column chromatography of dichloromethane (DCM) fraction of methanolic extract was used to isolate the alkaloids from AV. The isolated compounds were characterized by TLC, HPLC, ATR, HRMS, and NMR techniques. In-silico, studies were performed to investigate the interaction of the isolated compounds with cholinesterase enzymes (AChE and BuChE). Further, in-vitro assays were carried out to evaluate the AChE, BuChE, and Aβ inhibition properties. Propidium iodide displacement assay was performed to know the selectivity of isolated compounds at AChE PAS site. Furthermore, in-vivo studies were performed to evaluate memory and cognitive improvement against scopolamine-induced amnesia and Aβ induced neurotoxicity in rats. Results: A couple of leads were identified through bioactivity guided fractionation, such as vasicinone (VAS) and vasicine (VA) were responsible for the cholinesterase inhibition in DCM fraction. In-silico studies identified that both compounds exhibited stable interactions at AChE and BuChE active sites. VAS and VA inhibited the AChE, BuChE, and Aβ aggregation in-vitro studies and effectively displaced the propidium iodide at AChE PAS site. Further, in-vivo studies showed that administration of VAS and VA significantly improved the memory and cognitive dysfunction in scopolamine and Aβ induced cognitive and memory impairments in rats. Besides, both VAS and VA recovered the hippocampal cell density in AD rats. Moreover, VAS and VA did not show any sign of toxicity. Conclusions: The present study revealed that VAS acts as potent anti-AD agent from Adhatoda vasica Nees and it showed similar potency profile to VA against memory and cognitive impairment in AD. Both compounds VAS and VA possess strong potential in the preclinical development as natural drugs for anti-AD.